Low Pay Persistence in European Countries - Ken Clark; Nikolaos C. Kanellopoulos (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
Using panel data for twelve European countries over the period 1994-2001 we estimate the extent of state dependence in low pay. Controlling for observable and unobservable heterogeneity as well as the endogeneity of initial conditions we find positive, statistically significant state dependence in every single country. The magnitude of this effect varies by country, however this variation is not systematically related to labour market institutions.
Keywords: C23; C25; J31; J69; 330; Low pay; low pay persistence; state dependence; initial conditions; dynamic random effects probit models